The Intersection of Faculty Success and Student Success (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
When institutions put student success at the forefront, what does this mean for faculty?  While faculty may feel as if a focus on student success is in opposition to faculty success, the two are intertwined.  An understanding of the relationship between faculty and student success can assuage faculty concern regarding competition for attention and resources when faculty success and student success are juxtaposed.